2008
DOI: 10.1111/j.1525-1438.2007.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound and magnetic resonance imaging in staging of early cervical cancer

Abstract: The goal of this study was to determine the sensitivity, specificity, and accuracy of transrectal ultrasound (TRUS) in comparison to magnetic resonance imaging (MRI) in the evaluation of tumor volume, early parametrial infiltration, and identification of residual tumor in early-stage cervical cancer. Patients in whom an early-stage cervical cancer was diagnosed by clinical examination were enrolled in the study. Only those patients who were examined by both MRI and TRUS with following surgical treatment were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 30 publications
11
123
1
4
Order By: Relevance
“…However, several dedicated imaging centres, report high TVUS accuracy for cervical cancer staging and assessment of parametrial involvement, comparable to those of MRI [22,23] . Hybrid imaging (PET-CT or PET-MRI) is superior to conventional cross-sectional techniques for identifying metastatic lymph nodes, with excellent diagnostic accuracy, ranging from 85%-99% [24,25] .…”
Section: Parametrial Involvementmentioning
confidence: 94%
“…However, several dedicated imaging centres, report high TVUS accuracy for cervical cancer staging and assessment of parametrial involvement, comparable to those of MRI [22,23] . Hybrid imaging (PET-CT or PET-MRI) is superior to conventional cross-sectional techniques for identifying metastatic lymph nodes, with excellent diagnostic accuracy, ranging from 85%-99% [24,25] .…”
Section: Parametrial Involvementmentioning
confidence: 94%
“…Only a few studies have compared clinical examination, TRUS, and MRI pre-and post-therapy in cervical cancer. One of the largest studies so far including 95 patients with early stage cervical cancer, was published by Fischerova et al and it showed comparable accuracy of TRUS and MRI in pre-therapy patients and a superior accuracy of TRUS over to MRI in the post-therapy stage [27]. Pinkavova et al demonstrated that the accuracy of residual tumor detection in advanced stage cervical cancer after therapy is 77% for MRI and TRUS, and the sensitivity is 83% for TRUS and 96% for MRI [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fischerova et al compared TRU and MRI in early stage cervical cancer [8]. In a series of 95 cases, they reported that TRU was able to detect more clearly small cervical cancers (\1 cm [3]) than MRI and that TRU was more sensitive than MRI for detecting parametrial involvement (83 % vs 50 %).…”
Section: Transvaginal/transrectal Ultrasound For Local Staging Of Cermentioning
confidence: 99%